Which Role for a European Minister of Economy and Finance in a European Fiscal Union? - Zareh Asatryan; Xavier Debrun; Annika Havlik; Friedrich Heinemann; Martin G. Kocher; Roberto Tamborini (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
The European Commission has proposed to inaugurate a European Minister of Economy and Finance with the broad purpose of streamlining the complex and fragmented decision-making processes within the European Monetary Union. The Minister would jointly serve as Vice-President of the Commission and President of the Eurogroup, and have the tasks of coordinating budgetary instruments and structural reforms, designing and implementing adequate fiscal policies for the euro area, coordinating the enforcement of the Stability and Growth Pact, among others. This policy report discusses the potential role the Minister could play in the development of the European Fiscal Union. The report lays out the main challenges along the current institutional solutions facing several dimensions of the Fiscal Union, in particular related to fiscal sustainability, macroeconomic shocks, incentives of structural reforms, and the optimum provision of European public goods. The report then discusses whether and to what degree the new European Minister of Economy and Finance can provide appropriate solutions to these challenges for the Fiscal Union.
Keywords: 330